Human capital demand in Brazil: The effects of adjustment cost, economic growth, exports and imports - Joilson Dias (EconomiA, 2015)
The objective of this paper is to learn about the effects of the adjustment costs, economic growth, imports and exports on human capital labor demand. The dynamic model proposed by Sargent (1978) was adjusted to consider three types of human capital: (a) one with fundamental education (1–8 years of schooling); (b) one with secondary education level (9–11 years of education); (c) and one with tertiary education level (12 years or more of schooling). Using state level panel data, the dynamic econometrics estimates showed the following results: (i) the labor market adjustment costs are very higher; (ii) the adjustment cost for the human capital with intermediary education level is the highest one compared to the others; (iii) the states' economic growth favor those with superior education; (iv) the imports seems to favor the demand for those with intermediate education levels; (v) the degree of openness does show some weak effect on the demand for human capitals with intermediate education. In sum, the growing demand for human capital with some superior education seems to be more associated to its lower adjustment cost and economic growth; the non-significance of real wage elasticity and high adjustment cost seems to indicate that the human capital with intermediate knowledge is in short supply; hence, economic education policy that increases supply of such human capital are in need. – – O objetivo do artigo é o de avaliar os efeitos dos custos de ajustamento, do crescimento econômico, das importaç\~oes e das exportaç\~oes dos estados brasileiros sobre a evoluç\~ao do mercado de trabalho. O modelo dinâmico proposto por Sargent (1978) foi ajustado para contemplar o mercado de capital humano: a) com conhecimento fundamental (1 a 8 anos de estudos); b) com conhecimento intermediário (9 a 11 anos de estudos); c) e com conhecimento em nível superior (12 anos ou mais de estudos). As estimativas econométricas dinâmicas demonstraram os seguintes resultados: i) que os custos de ajustamento (contrataç\~ao) em geral s\~ao elevados nos estados brasileiros; ii) que os custos de ajustamento do capital com educaç\~ao em nível intermediáro é superior aos demais; iii) que o crescimento econômico dos estados favorece a demanda for capital humano com educaç\~ao superior; iv) que as importaç\~oes contribuem ainda que fracamente para com a demanda do capital humano com educaç\~ao interemdiária; v) que o grau de abertura econômica dos estados apresenta efeito muito fraco e instável sobre a demanda por capital humano com educaç\~ao intermediária. Em suma, o crescente aumento relativo do capital humano qualificado com educaç\~ao em nível superior parece estar mais associado ao seu menor custo de ajustamento (contrataç\~ao); o custo de ajustamento e a insignificância da elasticidade do salário real do capital humano intermediário parecem indicar uma possível restriç\~ao de oferta do mesmo; considerando que, aumentos da demanda de capital humano intermediário favorem a demanda pelos demais capitais humanos, portanto, políticas de formaç\~ao de pessoas com educaç\~ao intermediária devem ser incentivadas.
Keywords: J21; J23; J24; 330; Human capital; Adjustment cost; Economic growth; imports; Exports; Dynamic estimates; State panel data; Intertemporal elasticity